Strategies for the Prevention and Containment of Antibiotic Resistance - S.Y. Essack (South African Family Practice)
Antibiotic resistance may emerge by antibiotic selection pressure but is perpetuated by diverse risk factors and maintained within environments as a result of poor infection control. Population-specific drug pharmacokinetics and pharmacodynamics also play a role. The WHO, US, UK and EU have initiated strategies for the containment of resistance, with surveillance and delineation of the cause(s) cited as essential. Surveillance of antibiotic efficacy should be disease-based, establishing sensitivity profiles of common causative organisms to inform the development of or amendment to standard treatment guidelines and essential drugs lists adopted within the national drug policy. The manner of antimicrobial use (overuse, underuse, inadequate dosing) associated with resistance should be established for appropriate intervention in terms of rational drug use, a reduction in use and dosing regimens based on population-specific pharmacokinetics and pharmacodynamics. Risk factors unique to South African communities (poverty, HIV) and hospitals (duration of hospitalisation, location within the hospital, intensive care unit stay, surgery, wounds, previous and current antimicrobial therapy, mechanical ventilation, urinary catherterisation, nasogastric intubation, central venous and peripheral catheters, previous hospitalisation and transfer from another unit or hospital) must be determined and due vigilance exercised in patients exhibiting classical risk factors for the acquisition of or colonisation with resistant pathogens. Hygiene and sanitation (in communities) and infection control (in hospitals) status must be determined and interventions initiated to prevent the spread of resistance. Pharmacokinetics and pharmacodynamics specific to diverse populations must be devised to optimise antimicrobial therapy. South Africa has unique needs in the antimicrobial resistance arena, needs to be addressed in the context of severe financial, human resources and technological challenges.